Andraca yauichui sp. n., a new species endemic to mid elevation forests of Taiwan (Bombycidae sensu lato, Lepidoptera) - Wu, Shipher; Chang, Wei-Chun (Zootaxa, 2016)
A new endemic, montane species of the genus Andraca, A. yauichui sp. nov., in Taiwan is described. It can be separated well from a lower montane, notable tea tree pest A. theae (Matsumura, 1909), based on morphological characters of adult, e.g. larger wingspan size, head vertex white rather than brown, valval apex truncate rather than bifurcate, and final instar larva, e.g. the presence of a pair of white spot on lateral part of each abdominal segment and a distinct short anal horn rather than the absence of two characters. The subgeneric placement of this new species in Andraca is also discussed.